UNLOCKING THE POTENTIAL OF ISLAMIC SOCIAL FINANCE WITHIN THE ISLAMIC BANKING ECOSYSTEM FOR UNBANKED MSME INCLUSION - Reza Mustafa; Hermanto Siregar; Irfan Syauqi Beik; Suhendi; Rifki Ismal (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2026)
Despite the significant decline in poverty rates in Indonesia, the simultaneous shrinking of the middle class and the expansion of the vulnerable population reveal a persistent challenge of socio-economic inequality. Accessing formal financing remains a significant challenge for Micro, Small, and Medium Enterprises (MSMEs), as nearly 70% of them currently unbanked. Although Islamic banks are legally mandated to fulfill both commercial and social functions, their role in optimizing Islamic social finance instruments such as zakat and waqf to address the financing gap of unbanked MSMEs remains suboptimal. This study examines how Islamic social finance can be integrated with the Islamic banking ecosystem to support MSMEs and promote inclusive and sustainable economic development. This study adopts a descriptive analysis approach to explore stakeholder perceptions, experiences, and strategies. This study used secondary data combined with in-depth interviews (IDIs) with relevant stakeholders and focus group discussions (FGDs). This study suggests that Islamic banking in Indonesia develop a hybrid financing model that integrates commercial and Islamic social finance schemes to support MSMEs. MSMEs are segmented into subsistent, unbankable, pre-bankable, and bankable categories, with each segment requiring tailored financial instruments ranging from qard hasan to commercial contracts such as murabahah and musyarakah. Islamic banks and Islamic social finance institutions can form an ecosystem whereby banks act as orchestrators, and social institutions serve as program implementers. The findings emphasize that segment-based empowerment and strategic collaboration are essential to ensure sustainable MSME upgrading and inclusive financial development.